The asymmetric distribution of interphasic silver-stained nucleolus organizer regions in human and rat proerythroblasts - Smetana, K; Likovský, Z; Jirásková, I; Cermák, J (Folia biologica, 1999)
The distribution of SSPs representing AgNORs was studied in human as well as rat proerythroblasts to provide information on the distribution of these nucleolar components in highly immature and proliferating non-neoplastic cells. The distribution of SSPs was asymmetric and most of the cells contained one nucleolus which possessed a larger number of these nucleolar components than the remaining nucleoli. Such nucleolus might be functionally dominant, since the number of nucleolar SSPs is apparently related to the nucleolar biosynthetic activity. On the other hand, when a proerythroblast possessed only one nucleolus, the number of SSPs in such a cell was very similar to the sum of SSPs in a polynucleolar cell. The asymmetric distribution of SSPs characteristic for most proerythroblasts disappeared in the terminal stages of the erythroblastic development. Cells in such stages, as described previously, were characterized by the presence of a limited number of single SSPs.
Keywords: Erythropoiesis; Animals; Silver Staining; druhová specificita; Cell Nucleolus; organizátor jadérka; lidé; Bone Marrow; erytropoéza; Erythroid Precursor Cells; Species Specificity; kostní dřeň; Nucleolus Organizer Region; erytroidní prekurzorové buňky; krysa rodu Rattus; barvení stříbrem; zvířata; buněčné jadérko; Rats; Humans